2019
DOI: 10.1002/dys.1641
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic children need more robust information to resolve conflicting sensory situations

Abstract: The study involved investigating dyslexic children's postural control responses when visual and somatosensory cues were separately manipulated. Twenty dyslexic and 19 nondyslexic children performed a trial by standing upright inside a moving room and another by lightly touching a moving bar. Both trials lasted 240 s with the following three different stimulus characteristics: low (pretransition), high (transition), and low amplitude (posttransition). Body sway magnitude and the relationship between the movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…Then, the three types of SLD are presented: dyslexia (SWRD, SRCD), dyscalculia (SMLD) and dysorthographia (SWED). Each of these sections presented three movement categories (fine, gross and postural skills), assessed by different quantitative and qualitative motor tests [ 69 ], such as the first [ 70 ] and second edition [ 71 ] of the Test of Gross Motor Development (TGMD) [ 11 , 12 , 44 ], the first [ 6 ] and second editions of the Bruininks–Oseretsky Test of Motor (BOT) [ 38 , 56 , 72 , 73 ], the first and second version of Movement Assessment Battery for Children (M-ABC) [ 19 , 37 , 43 , 44 , 47 , 48 , 68 ], the Functional Mobility domain from the Pediatric Evaluation of Disability Inventory-Computer Adaptive Test (PEDI-CAT) [ 19 ], Spiral Drawing Test [ 15 ], Beery–Buktenica Developmental Test of Visual–Motor Integration [ 68 ], Leonard Tapping Task [ 45 ], Dysgraphia Scale [ 74 ], battery of clinical cerebellar tests [ 60 , 75 ], quiet standing paradigms [ 46 , 49 , 50 , 51 , 52 , 53 , 54 , 57 , 62 , 67 ], postural stability limits [ 41 ], Sensory Organisation Test [ 40 ], Multitest Equilibre [ 55 , 58 ], TechnoConcept ® platform [ 59 , 61 ], Motor Coordination Test [ 40 ], Chinese Handwriting Assessment Tool [ 63 ], ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then, the three types of SLD are presented: dyslexia (SWRD, SRCD), dyscalculia (SMLD) and dysorthographia (SWED). Each of these sections presented three movement categories (fine, gross and postural skills), assessed by different quantitative and qualitative motor tests [ 69 ], such as the first [ 70 ] and second edition [ 71 ] of the Test of Gross Motor Development (TGMD) [ 11 , 12 , 44 ], the first [ 6 ] and second editions of the Bruininks–Oseretsky Test of Motor (BOT) [ 38 , 56 , 72 , 73 ], the first and second version of Movement Assessment Battery for Children (M-ABC) [ 19 , 37 , 43 , 44 , 47 , 48 , 68 ], the Functional Mobility domain from the Pediatric Evaluation of Disability Inventory-Computer Adaptive Test (PEDI-CAT) [ 19 ], Spiral Drawing Test [ 15 ], Beery–Buktenica Developmental Test of Visual–Motor Integration [ 68 ], Leonard Tapping Task [ 45 ], Dysgraphia Scale [ 74 ], battery of clinical cerebellar tests [ 60 , 75 ], quiet standing paradigms [ 46 , 49 , 50 , 51 , 52 , 53 , 54 , 57 , 62 , 67 ], postural stability limits [ 41 ], Sensory Organisation Test [ 40 ], Multitest Equilibre [ 55 , 58 ], TechnoConcept ® platform [ 59 , 61 ], Motor Coordination Test [ 40 ], Chinese Handwriting Assessment Tool [ 63 ], ...…”
Section: Resultsmentioning
confidence: 99%
“…The design of these paradigms allowed for impairments in various sensory systems (visual, vestibular, proprioception, tactile) to be investigated, as well as multisensory integration for movement and postural control. These inputs are a very important part of movement and postural control and several studies have hypothesized that they could possibly be linked with motor skill impairments in SLDs [ 10 , 46 , 54 , 59 , 67 , 76 , 77 ]. However, to simplify the first screening of motor skills in children and adolescents with SLDs, our scoping review mainly reported results in the eyes-open condition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations